Mumps Disease Education For Students at Al-Abqory Islamic Boarding School - Audinos H Fernando Delezephs; Azlia Xaveria; Husnul Khotimah; Jeane Trifani; Sania Miutia Irmabillah Himawan; Andine Demetria Padmanegara Mashud; Chaerunnisa AR (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Mumps is an infectious disease that affects the parotid glands and is caused by the Paramyxovirus. Mumps can spread easily through droplet transmission. Many students at Al Abqory Islamic Boarding School have experienced mumps due to transmission from fellow students. The lack of knowledge about how to manage and prevent mumps has further worsened this condition Objective : The PINTAR GONZINI (Early Recognition and Response to Mumps Risk) program aims to enhance students' knowledge about mumps, enabling them to understand the necessary steps for managing and preventing the transmission of the disease. Research Methods/ Implementation Methods : The methodology employed in this activity consisted of health education delivered through lectures and utilizing several media, such as PowerPoint and leaflets. A total of 69 junior high school students from grades VII to IX participated in the implementation of this activity. Results : The results of the pre-test and post-test scores showed a significant increase in knowledge regarding mumps and the steps for its management and prevention. Conclusion/Lesson Learned : The findings of this activity indicate that health education methods are effective in improving students' knowledge regarding mumps